2006
DOI: 10.1111/j.1365-2656.2006.01058.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequentially assembled food webs and extremum principles in ecosystem ecology

Abstract: Summary1. Successional changes during sequential assembly of food webs were examined. This was carried out by numerical methods, drawing one species at a time from a species pool and obtaining the permanent (persistent) community emerging at each step. Interactions among species were based on some simple rules about body sizes of consumers and their prey, and community dynamics were described in terms of flows of biomass density. 2. Sequential assembly acted as a sieve on the communities, assembled communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Various features of randomly drawn communities have been shown to differ to communities drawn using sequential assembly rules (Virgo et al, 2006), while Haydon (2000) has demonstrated the conditions required to produce maximally stable communities. However, 5 randomly assembled communities have proven a popular starting point when asking questions of community stability (Chen and Cohen, 2001;Cohen and Newman, 1985;Ives and Hughes, 2002;Ives and Carpenter, 2007;Ives et al, 1999;Ives et al, 2000;Jansen and Kokkoris, 2003;Rozdilsky and Stone, 2001) and can serve as a useful null hypothesis for comparison with communities assembled under different ecological and evolutionary rules.…”
mentioning
confidence: 99%
“…Various features of randomly drawn communities have been shown to differ to communities drawn using sequential assembly rules (Virgo et al, 2006), while Haydon (2000) has demonstrated the conditions required to produce maximally stable communities. However, 5 randomly assembled communities have proven a popular starting point when asking questions of community stability (Chen and Cohen, 2001;Cohen and Newman, 1985;Ives and Hughes, 2002;Ives and Carpenter, 2007;Ives et al, 1999;Ives et al, 2000;Jansen and Kokkoris, 2003;Rozdilsky and Stone, 2001) and can serve as a useful null hypothesis for comparison with communities assembled under different ecological and evolutionary rules.…”
mentioning
confidence: 99%
“…This work also complements previous permanent-assembly algorithms by increasing the set of food web attributes for which the effect of permanence is known. Virgo et al (2006) measured the value of thermodynamic goal functions arising from permanence, whereas in this work, the structural attributes that are commonly used to verify the ordered-niche models are investigated instead. …”
mentioning
confidence: 99%
“…DOI: 10.1086/524953 step, according to some prespecified rules. There is already a large body of food web assembly literature (Tregonning and Roberts 1979;Post and Pimm 1983;Mithen and Lawton 1986;Taylor 1988;Drake 1990;Law and Blackford 1992;Luh and Pimm 1993;Law and Morton 1996;Lockwood et al 1997;Drossel et al 2001;Bastolla et al 2005;Virgo et al 2006) and a complimentary literature testing the predictions of the algorithms in experimental systems such as microcosms (Dickerson and Robinson 1986;Robinson and Dickerson 1987;Drake 1991;Wardle et al 1995;Moyle and Light 1996;Weatherby et al 1998;Chase 2003;Fukami 2004). Because assembly algorithms simulate invasion and extinction in a whole food web, they hold great promise for answering questions about succession, rehabilitation, and invasibility.…”
mentioning
confidence: 99%
See 2 more Smart Citations